Moodle-Based Sole (Self Organized Learning Environments) Model Implementation in Energy Transformation Material, Natural Science Subject for Fourth Grade Students - Meylisa Tri Mustika; Wati Sukmawati (Edumaspul: Jurnal Pendidikan, 2022)
This research mainly discusses about Moodle-based SOLE (Self Organized Learning Environments) model in natural science material about energy transformation. This research is conducted to give some suggestions regarding innovation alternatives that can be used during class activity, especially during this pandemic era. SOLE model itself was implemented after its contents had been matched with the website’s contents. From there, Moodle-based SOLE model was made and later, it was used in energy transformation material for fourth graders. This research includes results of this model’s testing that was conducted to fourth graders, precisely 29 of them. I obtained the data by using questionnaires. Then, all the data was analyzed with Likert Scale, quantitative approach. Later, we know that the overall feasibility value is 71%, so this model is feasible. In other words, the data we obtained shows that this model fulfills all the requirements to be considered feasible for in-class implementation.